2020
DOI: 10.1089/wound.2019.1045
|View full text |Cite
|
Sign up to set email alerts
|

Skin Microcolumns as a Source of Paracrine Signaling Factors

Abstract: We recently developed the approach of using ''microcolumns'' of autologous full-thickness skin tissue for wound repair. The small size of these micro skin tissue columns (MSTCs, *0.5 mm in diameter) allows donor sites to heal quickly without scarring. Treatment with MSTCs significantly accelerate wound healing, and suppled various skin cell types and skin structures to replenish the wound volume. This technology is now starting clinical use. In this study, we investigate whether MSTCs may also influence wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Adnexal structures such as hair follicles, eccrine glands and rete ridges contained within these columns allow the wounds to heal from within, rather than from the wound edges when full‐thickness wounds damage these important structures 32 . The inherent paracrine signalling within these skin microcolumns has also been found to have a potent stimulatory effect on wound healing, an added benefit to applying autologous skin columns to wounds 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adnexal structures such as hair follicles, eccrine glands and rete ridges contained within these columns allow the wounds to heal from within, rather than from the wound edges when full‐thickness wounds damage these important structures 32 . The inherent paracrine signalling within these skin microcolumns has also been found to have a potent stimulatory effect on wound healing, an added benefit to applying autologous skin columns to wounds 33 …”
Section: Discussionmentioning
confidence: 99%
“…32 The inherent paracrine signalling within these skin microcolumns has also been found to have a potent stimulatory effect on wound healing, an added benefit to applying autologous skin columns to wounds. 33 In addition to the implantation of FTSCs directly into the wound bed, we were also interested in determining the maximum amount of skin columns that could be harvested from a donor site while maintaining the integrity of the skin, and whether or not this affected donor site morbidity. As compared to STSGs.…”
Section: Discussionmentioning
confidence: 99%
“…Structural components of the skin, such as collagen and elastin networks, seem more likely for this role, and changes in mechanical properties when these extracellular networks are disrupted may be a contributing factor, as mechanotransduction pathways are known to be key mediators influencing long-term scarring versus regeneration in skin wounds (28). We have previously shown that MSTCs exhibited an altered paracrine production profile compared to FTSGs (29), and the results from the current study suggest that there are additional tissue-level effects related to the harvesting and/or morphology of MSTCs that are yet to be fully understood. Deciphering the underlying mechanism(s) governing this morphology dependency of the ability to preserve normal dermal architecture could be a critical step toward engineering physiologically normal full-thickness skin tissue.…”
Section: Discussionmentioning
confidence: 99%